Application Of Steam - Approach In Studying The Creativity And Life Of Zakhiriddin Muhammad Babur In Primary School (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The article explores the topic of using the STEAM approach in primary school. The importance of studying history in elementary school is revealed. An innovative example of studying the work and life of Zakhiriddin Muhammad Babur by future primary school teachers is considered.